Book Review: Deepak Bhojwani, Latin America, the Caribbean and India: Promise and Challenge. (December 2015) - Duarte, Carlos
Deepak Bhojwani, Latin America, the Caribbean and India: Promise and Challenge . New Delhi: Pentagon Press, 2012, pp. 212, ₹795.